Greening urban areas in line with population density and ecological zone can reduce premature mortality - Michael D. Garber; Tarik Benmarhnia; Weiqi Zhou; Pierpaolo Mudu; David Rojas-Rueda (Communications Earth & Environment)
Abstract Urban green space and urban compactness are each important principles for designing healthy, climate-resilient cities. The principles can co-exist, but greening may come at density’s expense if not considered deliberately. Existing studies estimating health impacts of greening scenarios have not considered what level of greenness is attainable for different population densities. Here, using the square kilometer as the unit of analysis, we estimate non-accidental mortality that could be prevented among adults older than 30 by greening that small area to a level of greenness assumed to be attainable based on its broader urban area (N = 15,917 globally), population density, and ecological zone. Results suggest a large potential for urban greening even in the most population-dense parts of cities such that on average 54 deaths per 100,000 could be prevented per year in those areas. That estimate may be about 25% higher or lower due to uncertainty in the underlying model.